2022
DOI: 10.1155/2022/6541026
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Silymarin and Gallic Acid against Cisplatin-Induced Nephrotoxicity and Hepatotoxicity

Abstract: Objective. This study aimed to investigate the effects of gallic acid and silymarin against nephrotoxicity and hepatotoxicity caused by cisplatin. Materials and Methods. In the study, 56 Wistar Albino rats were equally divided into eight groups. Group 1 was the control group; group 2 was the group receiving cisplatin; group 3 was the group receiving cisplatin + gallic acid; group 4 was the group receiving cisplatin + silymarin; group 5 was the group receiving cisplatin + silymarin + gallic acid; group 6 was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…CP causes oxidative stress by directly damaging mtDNA, which impairs appropriate expression of mitochondrial enzymes forming the respiratory chain, and thus induces oxidative stress" [40]. "The decrease in GSH level and antioxidant enzymes and increase in MDA due to oxidative stress are seen as the main reason for the toxicity caused by CP" [43].…”
Section: Discussionmentioning
confidence: 99%
“…CP causes oxidative stress by directly damaging mtDNA, which impairs appropriate expression of mitochondrial enzymes forming the respiratory chain, and thus induces oxidative stress" [40]. "The decrease in GSH level and antioxidant enzymes and increase in MDA due to oxidative stress are seen as the main reason for the toxicity caused by CP" [43].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the Introduction, oxidative stress is reportedly related to the deterioration of cats with CKD. 1,8,13,14 The evaluation of oxidative markers could have a deeper significance if there is an association between mortality and the levels of oxidative markers in cats, just as in humans. 7 In this study, 8-OHdG and MDA were identified as markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of oxidative stress contributing to the development and exacerbation of renal interstitial injury in rodent models with chronic kidney disease (CKD). 1 3 Oxidative stress in the kidney is also an important factor in the progression of CKD in cats. 4 Several biomarkers have been reported to reflect oxidative injury and pathogenesis of CKD in cats, for example liver-type fatty acid-binding protein (L-FABP), F2-isoprostane and transforming growth factor beta 1 (TGF-β1).…”
Section: Introductionmentioning
confidence: 99%
“…GA and its ester derivatives are widely used for an edible purposes, as flavoring agents, and as preservatives in the food industry [ 34 ]. Besides their edible use, there are diverse scientific reports on their biological and pharmacological activities, such as antioxidant, antibacterial, antiviral, anti-inflammatory, anticancer, and protective effects against cardiovascular, neuropsychological, gastrointestinal, and metabolic diseases [ 35 , 36 , 37 ]. The antitumor activity of GA is reported in various female cancers, such as its potentiating chemotherapeutic effect of paclitaxel in cervical cancer [ 38 ], while it is observed to potentiate paclitaxel and carboplatin effect in breast cancer [ 39 ].…”
Section: Phenolic Acids Involved In the Regulation Of Molecular Targetsmentioning
confidence: 99%